Treatment protocols for claw horn lesions and their impact on lameness recovery, pain sensitivity, and lesion severity in moderately lame primiparous dairy cows - Sadiq, Mohammed Babatunde; Ramanoon, Siti Zubaidah; Shaik Mossadeq, Wan Mastura; Mansor, Rozaihan; Syed-Hussain, Sharifah Salmah (Frontiers in Veterinary Science, 2022)
This randomised controlled trial was conducted to investigate the effects of routine treatment protocols for hoof horn disruptive lesions (HHDL) on lameness recovery rates, pain sensitivity, and lesion severity in moderately lame primiparous cows. First parity cows were recruited from a commercial dairy herd and randomly allocated to five groups (Four lame groups; A = 20, B = 21, C = 14, and D =15, and a non-lame group; E = 15). Eligibility criteria for the lame groups included a new lame score, presence of HHDL, good body condition score, and no history of previous lameness. Group A received a therapeutic trim, administration of a 3-day course of a non-steroidal anti-inflammatory drug (NSAID; Ketoprofen), and hoof block on the healthy claw. Groups B and C received the same treatment as Group A without hoof block and NSAID, respectively. Group D received only a therapeutic trim, whereas Group E received either a therapeutic or preventive trim. The enrolled cows were observed at weekly intervals, and the primary outcomes were assessed 28 days after treatment. The number (%) of recovered cows was 15 of 20 (75%), 13 of 21 (61.9%), 6 of 14 (42.9%), and 6 of 15 (40%) for Groups A, B, C, and D, respectively. Group A had significantly higher odds of successful treatment (OR = 4.5; 95% 1.1- 19.1) compared to Group D. Pain sensitivity based on limb withdrawal reflex was absent in a significantly higher number of cows (15/20; 75.0%) in Group A compared to Groups C and D. Group C had a significantly lower lesion severity score compared to Group B. Overall, cows with limb withdrawal at day 28 after treatment were less likely (OR = 0.06; 95% CI 0.01-0.24) to develop a non-lame score. In conclusion, the treatment with therapeutic trim, hoof block, and NSAID led to better recovery and reduced pain sensitivity in moderately lame primiparous cows with good BCS compared to those that received only therapeutic trim. Further research on the changes within the hoof capsule following various treatment protocols is needed to elucidate the clinical benefits observed in this study.